EVALUATION OF ENERGY SELLING COMPANY OPERATION RISKS - S. V. Grishkevich (Модернизация, инновация, развитие, 2016)
There are the following main operation risks typical for Russian power-selling companies (PSC): imperfection of legal documents related to functioning of such companies; lack of any officially approved calculation method for regulated tariffs of energy to population including uncertainty in the procedure of translating the energy to population at regulated costs; continuously growing debts on the part of energy consumers. Offered in the article is most effective PSC operation risk comparative estimation model. While comparing PSC operation risks typical for the energy provision industry, multiplication coefficients and other industry specific indices are to be used.